Vis/NIR optical biosensors applications for fruit monitoring - Wang, Meng; Xu, Yuanna; Yang, Yunyue; Mu, Boyu; Nikitina, Marina A.; Xiao, Xinqing (Biosensors and bioelectronics. X, 2022)
The global fruit industry is continually confronted with new technological challenges to meet people's material quality of life expectations. Fruit maturity has a strong association with the receiving time, transportation technique, and storage method of the fruit, and it has a direct impact on the fruit's quality. How to undertake rapid and non-destructive fruit quality testing has become a prominent topic in recent years. Because of its high repeatability, ease of operation, pollution-free, and measurement stability, visible and near-infrared (Vis/NIR) spectroscopy has become the most advanced non-destructive quality assessment technique in terms of equipment, applications, and data analysis methods in the field of non-destructive monitoring. An overview of the use of Vis/NIR optical biosensors in fruit internal quality monitoring and variety identification is presented. The benefits and drawbacks of various types of optical biosensors, as well as the practicality of various measurement modalities, are explored. Commonly used spectral biosensor data processing methods are summarized, including preprocessing, variable selection, calibration, and validation. Finally, the transition of pricey handheld NIR equipment to more cost-effective photodiode-based fruit maturity estimate devices was indicated as an issue for further investigation. •Vis/NIR optical biosensors applications for fruit quality monitoring were presented.•Spectral biosensor data processing methods were summarized.•More economical photodiode fruit maturity assessment equipment was presented.•Optical biosensors characteristics and practiaclly measurement modes were explored.